THE COMPARISON OF FINANCIAL PERFORMANCE USING DUPONT SYSTEM ANALYSIS IN PT KALBE FARMA TBK AND PT KIMIA FARMA TBK PERIOD 2011-2016 - Kaharmen, Pascal .; Worang, Frederik G.; Tielung, Maria . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Indonesia is a part of Association of South East Asia Nations (ASEAN) which means it has become open market that resulted the competition became fiercer and a company must be able to efficiently and effectively managing their asset. In Indonesia, there are some instability that happens on periods 2011 – 2016 like president election, politics, and cabinet changes that could affect Indonesian Stock Exchange.  This research aim to analyze the financial performance PT Kalbe Farma Tbk and PT Kimia Farma Tbk period 2011 – 2016  using DuPont System and compare those financial performance of both company. This research is classified as quantitative and used purposive sampling. The data were gathered from annual reports from both companies. Based on the result of the study, from the ROE perspective, PT Kalbe Farma Tbk is better from PT Kimia Farma Tbk. The researcher recommends that PT Kalbe Farma Tbk and PT Kimia Farma Tbk need to utilize their asset more, since from TAT both are decline each year and do a cost reduction for the raw materials. Keywords: financial performance, return on equity, return on asset, dupont system analysis, ratio analysis.